A revision of Thismia abei (Thismiaceae) endemic to Japan, with clarification of its flower structure and nomenclatural issues - Yudina, Sophia V.; Suetsugu, Kenji; Ikeda, Hiroshi; Sennikov, Alexander N.; Nuraliev, Maxim S. (Phytotaxa, 2026)
A comprehensive morphological and taxonomic revision of Thismia abei (Thismiaceae), a mycoheterotrophic species endemic to Japan, is presented. The history of its discovery and subsequent studies is overviewed, and the actual place of valid publication of its basionym, Glaziocharis abei, is established. The typification of T. abei is revised accordingly, and a drawing that illustrated the first documented record of the species is designated as a new lectotype. The current knowledge of the morphology of the species is updated based on new data on its floral anatomy, as follows. The inner tepals are confirmed to be postgenitally fused into a mitre. The stamens are shown to be united into a tube through perfect postgenital fusion. Each anther theca consists of two microsporangia, and the anther is thus tetrasporangiate. Each microsporangium dehisces by its own longitudinal slit. The pyramidal structure terminating the stylar column is demonstrated to consist largely of free styles (which are united into a tubular portion only at the base of this structure). The styles are proven to bear paired stigmas at their bases. For the first time, detailed photographs of the flower structure of T. abei are published herein. The current knowledge of the geographical distribution of the species is summarised and shown on a map. Its conservation status is assessed as Critically Endangered (CR).